Urban Health Performance as a Supporting Instrument for 'Sustainable Healthy Cities' in Sustainable Development Goals (SDGs) - Setiawan, Tomi; Mughits, Muhammad Hammam; Samith, Muhammad Farras (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This paper aims to analyze and explain the impact of urban development on public health with a focus on Bandung City, as well as the importance of health performance indicators to evaluate the effectiveness of urban health service delivery systems. Health performance indicators, such as mortality rates, morbidity rates, birth rates, and life expectancy, are critical in evaluating the success of health policies as well as identifying areas that need more attention. In Bandung City, despite an increase in population, the number of health service centers remains stagnant, leading to an imbalance between population growth and health service capacity. The research method used was mixed methods with descriptive statistical analysis from the Central Bureau of Statistics and in-depth interviews with informants from the Health Office and the community. The results showed that the imbalance between population growth and health service provision is a major challenge. Furthermore, performance evaluation with an appropriate measurement framework allows the identification of achievements, shortcomings, and challenges faced. Policy adaptation and strengthened cross-sector coordination have been shown to improve the health system's ability to respond to changing external conditions. Efforts to improve institutional capacity and appropriate resource allocation have led to improved efficiency and effectiveness of health management. In conclusion, the performance of health services in Bandung City has experienced complex dynamics but shows a trend of continuous improvement. Nevertheless, continuous monitoring and strategic interventions are still needed to maintain and improve the quality of health services in the future. Therefore, this study suggests the development of a longitudinal data-based performance evaluation model, strengthening the capacity of human resources in the health sector, and conducting interdisciplinary studies on socio-economic factors and public health behavior should be conducted to achieve more inclusive and sustainable development goals, in line with the SDGs, particularly SDG 3rd and SDG 11th.